Analysis of the Impact of Return on Assets, Current Ratio, Debt-to-Equity Ratio, and Firm Size on Firm Value (A Study of Infrastructure Companies Listed on the Indonesia Stock Exchange from 2019 to 2024) - Wilani, Resti Awalia; Pramudena, Sri Marti (INOVATOR, 2026)
This study aims to determine the effect of return on assets, current ratio, debt to equity ratio and company size on company value in infrastructure sector companies listed on the Indonesia Stock Exchange. The research period used is 6 years (2019–2024). The population used in this study is 15 companies. The sampling method used is the purposive sampling method. So that 90 observations were obtained. The research data were obtained from the Indonesia Stock Exchange website. The data analysis technique in this study used descriptive statistical analysis and hypothesis testing with panel data regression analysis. With the help of E-views 13 software. The results of this study partially indicate that Return on Assets (ROA), Current Ratio (CR) have a positive and significant effect on company value, Debt to Equity Ratio (DER) has a negative and significant effect on company value and Company Size does not affect company value.